Constant quest for quality: Digital cytopathology - Simone L Van Es; Janelle Greaves; Stephanie Gay; Jennifer Ross; Derek Holzhauser; Tony Badrick (Elsevier, 2018)
Background: Special consideration should be given when creating and selecting cytopathology specimens for digitization to maximize quality. Advances in scanning and viewing technology can also improve whole-slide imaging (WSI) output quality. Methods: Accumulated laboratory experience with digitization of glass cytopathology slides was collected. Results: This paper describes characteristics of a cytopathology glass slide that can reduce quality on resulting WSI. Important points in the glass cytopathology slide selection process, preparation, scanning, and WSI-editing process that will maximize the quality of the resulting acquired digital image are covered. The paper outlines scanning solutions which have potential to predict issues with a glass cytopathology slide before image acquisition, allowing for adjustment of the scanning approach. WSI viewing solutions that better simulate the traditional microscope experience are also discussed. Conclusion: In addition to taking advantage of technical advances, practical steps can taken to maximize quality of cytopathology WSI.